LEVEL OF PHUBBING BEHAVIOR IN CLASS IX STUDENTS OF SMP BHAKTI PRAJA PANGKAH - Muhammad Arif Budiman Sucipto; Rizka Nur Maulida (Adisam Publisher, 2024)
Phubbing is the behavior of deliberately ignoring the people around us to use or focus on the use of smartphones or other electronic devices. This study aims to determine the extent of students' phubbing behavior and provide suggestions for guidance and counseling service topics. The research method used is descriptive quantitative. The population in this study were students of class IX SMP Bhakti Praja Pangkah and the research sample involved the entire population with a total of 21 students with simple random sampling technique. Data collection techniques using questionnaires, observation and documentation. Data analysis techniques using percentage categorization techniques. The results showed that 15 students had phubbing behavior in the high category and 6 students had phubbing behavior in the medium category. There are 4 aspects of phubbing, namely aspects of nomophobia by 20.19%, interpersonal conflict by 47.76%, self isolation by 21.76% and problem acknowledge 23.05%. Meanwhile, in the statement item, the highest result of the 40 statement items is item number 7 with the statement “I am worried that if I don't open my cellphone I will miss important things”, obtaining an average result of 4.57%. The second order is item number 11 with an average result of 4.43%, namely the statement “People say that I use my cellphone too much”. Finally, in the statement “I feel anxious if I am away from my cellphone, item number 1 with an average result of 4.33%. Conclusion phubbing is a significant problem among adolescents in the school. Phubbing can be explained as a habit of ignoring people around by focusing attention on electronic devices, especially smart phones. The high level of phubbing behavior requires the right service as a prevention effort, the right service is through classical guidance services.